CESEB: A REPORT ON LATEST RESULTS - Hegedus, T.; Latkovic, O.; Markov, H.; Vince, I.; Cseki, A.; Nuspl, J.; Markova, N.; Rovithis-Livaniou, E.; Vinko, J. (Одеські астрономічні публікації, 2007)
Central-East-South European Binary star study group - CESEB - is an international research team focused on the study of binary stars through combined spectral and photometric observations that can be made using the Bulgarian NAO 2m telescope and several smaller telescopes located at various places in the Central East South European region. This paper is a report on our activities and results.